Impairment losses: the impact of the first-time adoption of the accounting standardization system In Portugal - Oliveira, J. (2018)
In 2010, Portuguese unlisted companies started to apply a new accounting frame of reference called Accounting Standardisation System (Sistema de Normalização Contabilística – SNC) based on IAS/IFRS. This paper seeks to analyse the impact of SNC first-time adoption regarding the accounting treatment of impairment losses. Portugal has been recognized as a Code-law country, with weak legal enforcement mechanisms, and conservative accounting practices. However, since 2005 Portuguese companies have been changing their financial reporting practices to a common-law institutional logic. Therefore, the present research setting might provide interesting insights to confirm if the differences found are due to management interests, rather than cultural issues. Differences found are neither due to cultural issues nor management interests. To mitigate political costs associated with their public visibility, larger companies present more credible financial statements that reflect their overall true financial and economic condition. This study is a valuable contribution to both the users of financial information and domestic standard-setters entities to help them understand and improve the impact of accounting standards. Consistent with Khalil and Simon (2014), it also contributes to the debate on the optimal flexibility permitted by International Financial Reporting Standards to improve reporting quality and reduce earnings management.